Differential MicroRNA Expression between T790M and L858R Mutated Lung Cancer - Ji Yeon Kim; Woo Jeong Lee; Ha Young Park; Ahrong Kim; Dong Hoon Shin; Chang Hun Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background MicroRNAs (miRNAs) are short, non-coding RNAs that mediate post-transcriptional gene regulation. They are commonly deregulated in human malignancies, including non-small cell lung cancer (NSCLC). The aim of this study is to investigate miRNA expression in T790M-mutated NSCLC resistant to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors. Methods Six cases of resected NSCLC harboring the T790M mutation were examined. We performed miRNA time polymerase chain reaction (PCR) array profiling using EGFR T790M-mutated NSCLC and L858R-mutated NSCLC. Once identified, miRNAs that were differentially expressed between the two groups were validated by quantitative real-time polymerase chain reaction (qRT-PCR). Results miRNA PCR array profiling revealed three up-regulated miRNAs whose expression levels were altered 4.0-fold or more in the EGFR T790M mutation group than in the L858R group: miR-1 (fold change, 4.384), miR-196a (fold change, 4.138), and miR-124 (fold change, 4.132). The three differentially expressed miRNAs were validated by qRT-PCR, and they were found to be overexpressed in the T790M group relative to L858R group. In particular, expression levels of miR-1 and miR-124 were significantly higher in the T790M group (p-value of miR-1 = .004, miR-124 = .007, miR-196a = .096). Conclusions MiR-1, miR-124, and miR-196a are overexpressed in EGFR T790M mutated NSCLC.